THE ADVERSARY EFFECT OF OBESITY ON ACADEMIC ACHIEVEMENT AMONG ADOLESCENTS - WALID ABU RAYYAN; IBRAHIM S AL-MAJALI; YAZAN BATARSEH; SHADI SALEM; WAEL ABU DAYYIH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This study aims to sough implications of the independent and combined demographic variables of weight status, age, food habits, and physical activity on academic achievement in adolescents. Methods: The study sample consisted of 940 male students in the second secondary class; four secondary schools from Hail city in the Kingdom of Saudi Arabia participated in this study during April 2017. Weight status was assessed through body mass index (BMI) (kg/m2). Participants filled the questioner to evaluate food habits and physical activity on academic achievement. Results: The mean weight was 74.21±17.36 kg interquartile range (IQR) (45–125), while the mean height was 171.27±7.37 cm IQR (140–193). The mean BMI was 33.73 (IQR 22.0–39.8). The overall prevalence of childhood obesity was 49.6% while the prevalence of overweight was 9.04%. The mean academic score for the second secondary class was 70±9.99 IQR (44–99). BMI has endorsed negatively on academic achievement (r=−0.322, p<0.05). Conclusion: We can summarize the independent variables as obesity ameliorates academic achievement in a counteractive way; high BMI affects total academic score in a negative pattern, whereas practicing mental games influenced positively the academic achievement and performance.